Pelatihan Intensif Strategi Pendampingan Pengembangan Masyarakat - Tampubolon, Yohanes Hasiholan; Christantie, Mareta; Viktor, Yulianus; Selan, Yustus; Warum, Samuel (Society : Jurnal Pengabdian Masyarakat, 2024)
Holistic service in Christian theology emphasizes the integration of social service and evangelism as integral parts of the church's mission. Participant-centered training methods, such as LePSAS, are utilized to facilitate participant-oriented learning. These activities employ LePSAS training methods applied in community service activities to equip participants with knowledge and skills concerning holistic service. Activity evaluations indicate that participants gain a deeper understanding of holistic service and community development. Despite challenges such as field practice session cancellations, participants are still able to implement their learning in their service contexts. The implementation of holistic service through LePSAS training methods contributes positively to expanding participants' understanding and skills in applying holistic service. Activity evaluations serve as a foundation for developing more effective training programs in the future. Thus, these activities underscore the importance of holistic service in the context of Christian theology and the effectiveness of participant-centered training methods in strengthening holistic service.